Ducks foraging on swan faeces - Shimada, T (Wildfowl, 2012)
Foraging on avian faeces by birds is uncommon apart from the consumption of nestling faeces by songbird parents. Here, observations made of five Mallard Anas platyrhynchos, three Green-winged Teal A. crecca and one Baikal Teal A. formosa seen feeding on Whooper Swan Cygnus cygnus faeces, on the ice in Lake Izunuma, Japan, on 10 February 2010, are described. The faeces of herbivorous Whooper Swans contained undigested vegetation which, when dissolved in water on top of the ice, was available for consumption by the ducks.